Human monoclonal anti-MAG antibody and anti-Leu 7 recognise shared antigenic determinants in peripheral nerve and spinal cord. Issue 7 (July 1985) - Stoll, G; Schwendemann, G; Heininger, K; Steck, A J; Toyka, K V
Abstract : Anti-Leu 7 monoclonal antibody (MAB), a marker of natural killer cells, and a human MAB to myelin-associated glycoprotein (MAG) from a patient with a demyelinating neuropathy specifically stained Schmidt-Lanterman incisures, paranodal and periaxonal regions in peripheral nerve myelin by immunocytochemistry on thin plastic sections, while compact myelin was labelled in paraffin-embedded material. Preabsorption studies indicated that the antigen recognised was a MAG epitope shared by MAG and Leu 7. In spinal cord both MABS bound to oligodendrocytes and a subclass of anterior horn cells. Our findings support the hypothesis that shared antigens between the nervous and the immune systems do exist in situ, which may be important in the pathogenesis of demyelinating neuropathies with monoclonal gammopathies.